Gold Finger: Metal Jewellery as a Disease Modifying Antirheumatic Therapy! - T. Hlaing; S. Ramteke; K. Binymin (Case Reports in Medicine)
Polyarticular psoriatic arthritis is a chronic, progressive and disabling auto-immune disease often affecting the small joints of the hands in a symmetrical fashion. The disease can progress rapidly causing joint swelling and damaging cartilage and bone around the joints resulting in severe deformities. We report a very unusual case of a 49-year-old woman who presented with polyarticular psoriatic arthritis affecting all proximal interphalangeal (PIP) joints of both hands except the left ring finger PIP joint. On clinical examination there was no evidence of arthritis in the left ring finger PIP joint. We confirmed the paucity of joint damage in the PIP joint of the left ring finger using more modern imaging modalities such as musculoskeletal ultrasound and MRI scan of the small joints of the hands. All other PIP joints in both hands demonstrated advanced degrees of joint damage secondary to chronic psoriatic inflammatory arthritis. We postulated that wearing a gold wedding ring has helped protecting the PIP joint of the left ring finger from the damaging effect of inflammatory arthritis. The possible mechanisms by which metal jewellery (gold ring) confer protection to adjacent joints was discussed.